2017
DOI: 10.18632/oncotarget.16545
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of AFAP1-AS1 and PD-1 predicts poor prognosis in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) carries a high potential for metastasis and immune escape, with a great risk of relapse after primary treatment. Through analysis of whole genome expression profiling data in NPC samples, we found that the expression of a long non-coding RNA (lncRNA), actin filament-associated protein 1 antisense RNA 1 (AFAP1-AS1), is significantly correlated with the immune escape marker programmed death 1 (PD-1). We therefore assessed the expression of AFAP1-AS1 and PD-1 in a cohort of 96 paraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 84 publications
1
89
0
Order By: Relevance
“…Fortunately, the emerging microarray and next-generation sequencing technology help us gain deeper insight into the thousands or millions of human genome sequences concurrently [22][23][24][25][26][27][28][29][30]. As a consequence, these related technologies have been adopted extensively to screen the potential diagnostic indicator and treatment target points for multiple diseases, such as cancer, and metabolic disease [31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the emerging microarray and next-generation sequencing technology help us gain deeper insight into the thousands or millions of human genome sequences concurrently [22][23][24][25][26][27][28][29][30]. As a consequence, these related technologies have been adopted extensively to screen the potential diagnostic indicator and treatment target points for multiple diseases, such as cancer, and metabolic disease [31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical analysis revealed that PD-1 and AFAP1-AS1 were co-expressed in the TILs of the NPC tissues. Patients with NPC exhibited poor prognosis when the tumor was positive for both AFAP1-AS1 and PD-1 (74). TIM-3 expressed on the CD8 + T lymphocytes is reported to be correlated with the phenotype of immune exhaustion.…”
Section: Lymphoid Immune Cellsmentioning
confidence: 99%
“…lncRNAs, which are up-regulated in NPC, may act as oncogene to promote growth, migration, invasion, chemo-, and radio-resistance, while others may possess anti-tumor properties [42-48] (Fig. 1).…”
Section: Lncrnas In Npcmentioning
confidence: 99%